Identification and Morphometric Analysis of Toxocara cati in Domestic Cat at Ontosenovet Animal Clinic Malang: Identifikasi dan Analisis Morfometri Toxocara cati pada Kucing Domestik di Klinik Hewan Ontosenovet Malang - Soegiarto, Ellen; Yesica, Reza; Antika, Dona Dwi (Faculty of Veterinary Medicine Universitas Brawijaya, 2022)
Toxocariasis is a worm disease caused by infection of Toxocara cati. This study aims to identify the etiology, clinical symptoms, diagnosis, morphometry of eggs and worms in domestic cats at the Ontosenovet Animal Clinic Malang. The results of physical examination reveal enlargement of the abdomen, dull hair and hair loss. Hematological examination results showed a decrease in platelets, RDW-VC, and RDW-SD, an increase in lymphocytes, and MCHC. Examination of feces and worms and eggs is carried out at the Parasitology Laboratory of the Faculty of Veterinary Medicine, Universitas Brawijaya. Stool examination is carried out using native and floating methods which showed the presence of worm eggs in the second method. The eggs show a slightly elongated or oval shape, thick walls, and a mottled surface. Worm eggs have an average length of 71,61 μm and a width of 59,87 μm. Worms obtained from cat vomit were then made preparations with Acetocarmine staining. The results of worm observations show three lips on the anterior, posterior end of digitiform and curved to the ventral. The results of morphometric measurements of adult T. cati show that the diameter of the worm, the length of the posterior end of the worm, and the width of the lips obtained an average of 754,14 μm, 545,19 μm, and 314,87 μm respectively. Overall body lengths of worm samples 1, 2, and 3 are 7,50 cm, 8,70 cm, and 7,80 cm with an average of 8,00 cm. Based on the examination the cat had toxocariasis due to Toxocara cati. The therapy given is an anthelmintic Drontal® (¾ tablet) which contained 20 mg praziquantel and 80 mg pyrantel.